Conocimiento y manejo de transfusión de sangre y sus componentes en el profesional de Enfermería del Hospital Teófilo Dávila. - Jiménez Rodríguez, Karina del Cisne (2018)
The present research work determined the knowledge and management of blood transfusion and its components of nurse professionals of the Hospital Teófilo Dávila period 2017-2018. This procedure is a usual practice in the hospital environment, and it is estimated that approximately 85 million of transfusions are performed in the worldwide during the year, in which the role of the nurse is fundamental; it is necessary specific knowledge for the administration. In addition with continuous updates to provide the patient the quality and safety that it requires. This research is a cross-sectional descriptive study, the integrants that participated on that were 151 nurse professionals that work in this health house. The information was obtained by two instruments: a quiz, which measures the knowledge of the professional, and an observational instrument to verify the handling of blood transfusion, and its components, demonstrating that, the majority of professionals have a regular level of knowledge, a good level of 27% ,and a poor level of 16%. Inside of the management of transfusion it is demonstrated that there is a significant level of 35%, a partial management of 33%, an excellent management of 13%, insufficient represented by 10% and a minimum of 8%. Key words: components, nursing, professional, blood, transfusion